Spatial design features to enhance social interaction among residents of a low-rise neighbourhood in Basra, Iraq - Alahmed, Hani Ahmed Hussein (2012)
The planners of the Municipal of Basra have issued a rationalization of land use and encouraged developers to use low-rise residential neighbourhood. However, solving the problem of lack of lands for housing leads to other problems. The communities who are living in the low-rise residential neighbourhood do not interact with one another. The main objective of this study is to identify the significant characteristics of spatial design configuration, which influence the residents’ social interaction in order to solve the lack of residents’ satisfaction in low-rise residential buildings in a neighbourhood. The contribution of this study examines the spatial characteristics of built environment (secured, collective, supportive, responsive spaces) by extending the use of multiple regression models to analyse the spatial characteristics that could affect the residents’ social interaction. The first objective, to understand the effect of built environment on the social interaction achieved by clarifying the literature review of both western communities and Arab-Muslims communities. The questionnaires used to achieve the second objective of this study that is to analyse the feedback of the low-rise residential neighbourhood residents and the level of social interaction among residents. The study used multiple linear regressions to examine the influence of spatial characteristics of built environment on social interaction. The study concludes that the existence of specific characteristics may enhance social interaction of the residents. These characteristics are hierarchical spatial structure,physical security supports, fostering proper proximity and accessibility, supporting predisposition and motivations, supporting socio-cultural behaviour characteristics,supporting residents’ needs and activities, and increasing permeability. This result came up from the questionnaires. This study significantly contributes to the field of housing. The study clarified the theories of social interaction among the residents in both the western and Arab-Muslim communities. The study identified the spatial characteristics that could reinforce social interaction among the residents.